Viri mednarodnega kazenskega prava - Škrk, Mirjam (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2011)
International criminal law (ICL) is a relatively new legal discipline which is in the view of the authoress closely related to public international law. The underlying reason for this assumption lies in the fact that three inherent international criminal courts are functioning in the international community, namely the two ad hoc tribunals for former Yugoslavia (ICTY) and Rwanda (ICTR) and the International Criminal Court (ICC). The case-law of these courts proves that international law as part of ICL prevails in their proceedings. Therefore Article 38 (I) of the International Court of Justice has been used as a starting point to analyze the sources of ICL. Although this provision is helpful as far as it concerns the categorization of the main sources (treaties, rules of customary international law, general principles of law) and the subsidiary ones (case-law, legal theory), it has its deficiencies when applied in the ICL. Namely, the main preoccupation of the ICL is the criminal accountability of individuals for the most heinous crimes. Therefore, the principle of legality must prevail in the ICL. One of the shortcomings of the Statutes of the ICTY and ICTR is the absence of the rule on sources. This was overcome by the Rome Statute of the ICC which contains the provision on applicable law in Article 21.
Keywords: international law; mednarodno pravo; mednarodno kazensko pravo; international criminal law; sources of international (criminal) law; viri; international criminal courts; mednarodna kazenska sodišča